Diversity of Fern Species (Pteridophyta) in Sipeso Village, Sindue Tobata District, and Their Utilization as Learning Media - Ahsyaban; Lilies N. Tangge; Mohamaad Jamhari (Equator Science Journal, 2024)
Biodiversity is very high, both in flora and fauna, and this abundance should be utilized for community needs. One of the biological potentials is the natural resource of flora, including ferns (Pteridophyta). This study aims to describe the abundance of fern species (Pteridophyta) found in the plantations of Sipeso Village, Sindue Tobata District, and to use the results as an educational medium in the form of a flipbook suitable for use. This type of research is descriptive quantitative, with the research location determined through purposive sampling, selecting two observation stations. Sampling was conducted using line transects with a plot method, with a research area of 5000 m², where each station covers 2500 m². In each station, a 50-meter line transect was placed, and plots of 10m x 10m were systematically arranged using a zig-zag method. Samples within the plots were then collected. The results showed that 12 species of ferns were found, which belong to the class Polypodiopsida, including 2 orders and 8 families. Based on their habitat, 8 species of terrestrial ferns and 4 species of epiphytic ferns were identified. The abundance of fern species (Pteridophyta) in the Sipeso Village plantations is classified as low with an abundance value of R1 = 1.76. The percentage of the educational media’s suitability is 83.25%, indicating that the flipbook as an educational medium is highly suitable for use.